LIMIT

Tentukan nilai limit berikut:
( x3 − 1) ( x3 + 1)
x6 − 1
= lim
=2
1. lim 3
x →1 x − 1
x→1
x3 − 1
2x2 + x − 6
x →−2 4
−8 x + 3 4 x

2. lim

( x + 2)(2 x − 3)
= lim 4
.
x →−2
−8 x + 3 4 x
= lim

x →−2

= lim

−8 x − 3 4 x
4
−8 x − 3 4 x

4

( x + 2)(2 x − 3)( 4 −8 x − 3 4 x )
−8 x − 3 16 x 2

.

−8 x + 3 16 x 2
−8 x + 3 16 x 2

( x + 2)(2 x − 3)( 4 −8 x − 3 4 x )( −8 x + 3 16 x 2 )
−8 x − 3 256 x 4

x →−2

( x + 2)(2 x − 3)( 4 −8 x − 3 4 x )( −8 x + 3 16 x 2 )
= lim
x →−2
−8 x − 4 x 3 4 x
( x + 2)(2 x − 3)( 4 −8 x − 3 4 x )( −8 x + 3 16 x 2 )
= lim
.
x →−2
−4 x( 3 4 x + 2)

3

16 x 2 − 2 3 4 x + 4

3

16 x 2 − 2 3 4 x + 4

( x + 2)(2 x − 3)( 4 −8 x − 3 4 x )( −8 x + 3 16 x 2 )( 3 16 x 2 − 2 3 4 x + 4)
x →−2
−4 x(4 x + 8)

= lim
= lim

( x + 2) (2 x − 3)( 4 −8 x − 3 4 x )( −8 x + 3 16 x 2 )( 3 16 x 2 − 2 3 4 x + 4)

x →−2

=

−7.4.8.12
= −84
−16. − 2

( x3 − 27)( x 3 + 27)
3. lim
3
x →3
4 x − 3 12

−16 x ( x + 2)

( x − 3)( x 2 + 3x + 9)( x3 + 27) 3 16 x 2 + 3 48 x + 3 144
= lim
.
3
3
x →3
4 x − 3 12
16 x 2 + 3 48 x + 3 144
( x − 3)( x 2 + 3x + 9)( x3 + 27)( 3 16 x 2 + 3 48 x + 3 144)
x →3
4 x − 12

= lim
= lim

( x − 3) ( x 2 + 3x + 9)( x3 + 27)( 3 16 x 2 + 3 48 x + 3 144)
4 ( x − 3)

x →3

27.54.3 3 144 2187 3
=
=
144
4
2
(2 − 3 x )( 4 2 x + 2)
4. lim
x →8 4
( 2 x − 2)(2 + 3 x )
(2 − 3 x )( 4 2 x + 2) 4 + 2 3 x + 3 x 2
= lim 4
.
.
x →8 ( 2 x − 2)(2 + 3 x )
4 + 2 3 x + 3 x2
= lim
x →8

= lim
x →8

= lim
x →8

=

(8 − x)( 4 2 x + 2)( 4 2 x + 2)
( 2 x − 4)(2 + 3 x )(4 + 2 3 x + 3 x 2 )

(8 − x)( 4 2 x + 2)( 4 2 x + 2)( 2 x + 4)
(2 x − 16)(2 + 3 x )(4 + 2 3 x + 3 x 2 )
− ( x − 8) ( 4 2 x + 2)( 4 2 x + 2)( 2 x + 4)
2 ( x − 8) (2 + 3 x )(4 + 2 3 x + 3 x 2 )

−4.4.8
16
4
=− =−
2.4.12
12
3

5. lim
x →1

.

x3 − 3 x
x5 ( 4 x3 − x 2 )

4
4

2x + 2
2x + 2

2x + 4
2x + 4

= lim
x →1

= lim
x →1

= lim
x →1

= lim
x →1

= lim
x →1

=

x3 − 3 x
x5 ( 4 x3 − x 2 )

.

x6 + x3 3 x + 3 x 2

.

x6 + x3 3 x + 3 x 2

( x9 − x)( 4 x3 + x 2 )
x5 ( x 3 − x 4 )( x 6 + x 3 3 x + 3 x 2 )

.

4

x3 + x 2

4

x3 + x 2

x3 + x 4
x3 + x 4

( x9 − x)( 4 x3 + x 2 )( x 3 + x 4 )
x5 ( x3 − x8 )( x 6 + x 3 3 x + 3 x 2 )
x( x8 − 1)( 4 x 3 + x 2 )( x 3 + x 4 )
− x8 ( x5 − 1)( x 6 + x3 3 x + 3 x 2 )
x ( x − 1) ( x 7 + x 6 + x 5 + x 4 + x 3 + x 2 + x + 1)( 4 x 3 + x 2 )( x 3 + x 4 )
− x8 ( x − 1) ( x 4 + x 3 + x 2 + x + 1)( x 6 + x 3 3 x + 3 x 2 )

1.8.2.2
32
=−
−1.5.3
15

6. lim
x →1

( x 6 − 4 x3 + x + 2)( x 6 − 2 x 3 + 1)
( x − 1)( x 2 − 1)(1 + 3 x + 3 x 2 )

= lim
x →1

( x − 1)( x5 + x 4 + x3 − 3x 2 − 3 x − 2)( x 3 − 1) 2
( x − 1)( x − 1)( x + 1)(1 + 3 x + 3 x 2 )

.

x +1 1− 3 x
.
x +1 1− 3 x

( x − 1)( x5 + x 4 + x3 − 3x 2 − 3 x − 2){( x − 1)( x 2 + x + 1)}2 ( x + 1)(1 − 3 x )
x →1
( x − 1)( x − 1)( x + 1)(1 − x)

= lim
= lim

( x − 1) ( x 5 + x 4 + x3 − 3 x 2 − 3 x − 2) ( x − 1) 2 ( x 2 + x + 1) 2 ( x + 1)(1 − 3 x )

x →1

=

− ( x − 1) ( x − 1) ( x + 1) ( x − 1)

−5.9.2.0
=0
2

x2 + 2 x + 1 − x2 + 2 x + 1
x →∞
x2 + 2x + 1

7. lim
=

1+ 0 + 0 − 0 + 0 + 0
=1
1+ 0 + 0

Tentukan Nilai a dan b jika:
3 − ax + b 4
=
x →2 4
8x − 2 x 3

8. lim

3 − 2a + b = 0
9 = 2a + b
b = 9 − 2a
3 − ax + 9 − 2a 4 8 x + 2 x 3 + ax + 9 − 2a 4
.4
.
=
4
x →2
8x − 2x
8 x + 2 x 3 + ax + 9 − 2a 3

lim

(9 − a ( x − 2) − 9)( 4 8 x + 2 x ) 8 x + 2 x 4
lim
.
=
x →2
( 8 x − 2 x)(3 + a( x − 2) + 9) 8 x + 2 x 3
lim
x →2

−a ( x − 2) ( 4 8 x + 2 x )( 8 x + 2 x)
−4 x ( x − 2) (3 + a ( x − 2) + 9)

=

4
3

−a.4.8 4
=
−8.6 3
a=2
b = 9 − 2a = 5
( x − 1)(bx + 1) + 3 x − 1
=1
x →1
x 2 + 2ax + a 2

9. lim

1 + 2a + a 2 = 0
(a + 1) 2 = 0
a = −1
( x − 1)(bx + 1) + 3 x − 1 3 x 2 + 3 x + 1
lim
.
=1
3 2
x →1
x2 − 2 x + 1
x + 3 x +1
lim
x →1

lim
x →1

( x − 1)(bx + 1)( 3 x 2 + 3 x + 1) + x − 1
( x − 1)( x − 1)( 3 x 2 + 3 x + 1)
( x − 1) {(bx + 1)( 3 x 2 + 3 x + 1) + 1}
( x − 1) ( x − 1)( x + x + 1)

(b + 1).3
=1
0.3
b = −1

3

2

3

=1

=1